Reversible host-guest crosslinks in supramolecular hydrogels for on-demand mechanical stimulation of human mesenchymal stem cells - Linke, Philipp; Munding, Natalie; Kimmle, Esther; Kaufmann, Stefan; Hayashi, Kentaro; Nakahata, Masaki; Takashima, Yoshinori; Sano, Masaki; Bastmeyer, Martin; Holstein, Thomas W.; Dietrich, Sascha; Müller-Tidow, Carsten; et al. (Advanced healthcare materials, 2024)
Stem cells are regulated not only by biochemical signals but also by biophysical properties of extracellular matrix (ECM). The ECM is constantly monitored and remodeled because the fate of stem cells can be misdirected when the mechanical interaction between cells and ECM is imbalanced. A well-defined ECM model for bone marrow-derived human mesenchymal stem cells (hMSCs) based on supramolecular hydrogels containing reversible host-guest crosslinks is fabricated. The stiffness (Young's modulus E) of the hydrogels can be switched reversibly by altering the concentration of non-cytotoxic, free guest molecules dissolved in the culture medium. Fine-adjustment of substrate stiffness enables the authors to determine the critical stiffness level E* at which hMSCs turn the mechano-sensory machinery on or off. Next, the substrate stiffness across E* is switched and the dynamic adaptation characteristics such as morphology, traction force, and YAP/TAZ signaling of hMSCs are monitored. These data demonstrate the instantaneous switching of traction force, which is followed by YAP/TAZ signaling and morphological adaptation. Periodical switching of the substrate stiffness across E* proves that frequent applications of mechanical stimuli drastically suppress hMSC proliferation. Mechanical stimulation across E* level using dynamic hydrogels is a promising strategy for the on-demand control of hMSC transcription and proliferation. Supramolecular hydrogels containing reversible host-guest crosslinks allow on-demand mechanical stimulation of human mesenchymal stem cells across the critical stiffness level E* at which the mechano-sensory signaling pathway is turned "on/off" both in situ and ex situ. The switching of the substrate stiffness across E* beyond a certain frequency drastically suppresses the stem cell proliferation without losing the multipotency.image